(untitled) (Indian Journal of Child Health, 2024)
Objective: This study aims to determine the correlation between clinical as well as laboratory profile changes with the outcome of acute encephalitis syndrome (AES) cases. Materials and Methods: This prospective observational study was conducted in the Department of Pediatrics at Jorhat Medical College and Hospital, Assam over a period of 1 year where 49 diagnosed cases of AES in children aged between 1 month and 12 years were enrolled. Results: The study found that fever (100%) and altered sensorium (100%) were the most common clinical presentations in AES cases, followed by seizure (63%), headache (34.7%), vomiting (26.5%), diarrhea (22.4%), etc. Japanese encephalitis (JE) was the most common cause of AES (28.6%), followed by herpes simplex virus (4.1%), pyogenic meningitis (4.1%), and tubercular meningitis (2%), etc. However, the majority of cases (61.2%) were found to have an unknown etiology. Among the 49 cases, 27 (55.1%) recovered without neurological sequelae, 8 (16.8%) had neurological sequelae, and 14 (28.6%) died during the course of treatment. The most common neurological sequelae observed were motor deficit (37.5%), behavioral disorders, aphasia (25% each), and cranial nerve palsy. Glasgow coma scale (GCS) at the time of admission and during the time of hospital stay was found to have a significant (p<0.05) correlation with outcome in AES patients. Conclusion: The study concludes that AES cases commonly present with fever, altered sensorium, seizure, headache, vomiting, and signs of meningeal irritation. JE remains a major known cause of AES in children in this region of India. GCS at the time of admission and during the time of hospital stay were found to have a significant correlation with outcome. The neurological sequelae highlight the need for global attention to combat them save the lives of children.